2019
DOI: 10.1007/s42452-019-0642-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of synthesis approaches for tuning the photocatalytic property of ZnO nanoparticles

Abstract: Tuning the photocatalytic property of zinc oxide (ZnO) nanoparticles (NPs) is timely. Dependence of photocatalysis upon size, morphology and effective surface area of the particles used has led to optimization in various synthesis procedures. The current article addresses to dictate a cost-effective, bio-friendly, modified ease-process for this issue. The synthesis of ZnO NPs with differing photophysical properties, sizes and morphologies, in order to tune its photocatalytic activity, have been extensively stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(28 citation statements)
references
References 71 publications
4
18
0
Order By: Relevance
“…The hexagonal wurtzite structure is confirmed from the typical diffraction peaks for (1 0 0), (0 0 2), and (1 0 1) planes located at 32.5, 35.5, and 37.3° of 2θ, respectively, with a high degree of crystallization and approximately similar to the standard data of pure ZnO ( a = 3.2488 Å, c = 5.2061 Å, space group P 63 mc ) and very well-matched with JCPDS # 36-1451. 20 The XRD spectrum shows three broad peaks indexed as (1 0 0), (0 0 2), and (1 0 1) for each sample, showing that the nature of the prepared nanoparticles is polycrystalline. In all the samples, nine major peaks are observed, which are indexed as (1 0 0), (0 0 2), (1 0 1), (1 0 2), (1 1 0), (1 0 3), (2 0 0), (1 1 2), and (2 0 1) with maximum diffraction intensity at (1 0 1) lying between 35.8 and 37.6°.…”
Section: Resultsmentioning
confidence: 92%
“…The hexagonal wurtzite structure is confirmed from the typical diffraction peaks for (1 0 0), (0 0 2), and (1 0 1) planes located at 32.5, 35.5, and 37.3° of 2θ, respectively, with a high degree of crystallization and approximately similar to the standard data of pure ZnO ( a = 3.2488 Å, c = 5.2061 Å, space group P 63 mc ) and very well-matched with JCPDS # 36-1451. 20 The XRD spectrum shows three broad peaks indexed as (1 0 0), (0 0 2), and (1 0 1) for each sample, showing that the nature of the prepared nanoparticles is polycrystalline. In all the samples, nine major peaks are observed, which are indexed as (1 0 0), (0 0 2), (1 0 1), (1 0 2), (1 1 0), (1 0 3), (2 0 0), (1 1 2), and (2 0 1) with maximum diffraction intensity at (1 0 1) lying between 35.8 and 37.6°.…”
Section: Resultsmentioning
confidence: 92%
“…TiO 2 and ZnO followed JCPDS No. 73-1764 and 36-1451, respectively (Basnet et al, 2019) . The structure of Ni/Al-LDH, TiO 2 , and ZnO in composite Ni/Al-TiO 2 and Ni/Al-ZnO was consistent, which also indicated that the preparation of composite did not change the form of precursors (see Figures 2d and 2e).…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, the specific surface areas of the calcined samples are The PXRD diagrams for the calcined samples are included in Figure 1. The peaks of the LDH structure are no longer recorded, and the positions of the peaks are very close to those of ZnO, zincite (JCPDS standard n • 36-1451) [31].…”
Section: Characterization Of the Samplesmentioning
confidence: 91%